Optimization of Benefit Allocation in Contracted Water-Saving Projects Based on the Shapley Value Method. (23rd June 2022) - Zhu, Jiwei; Wang, Jiangrui; Zhu, Tingting; Zhai, Zhao; Zhao, Xin
Abstract : Contracted water-saving management (CWSM) has emerged as a powerful model for water-saving actions. In a CWSM project, whether the benefit allocation among the stakeholders is fair and reasonable will affect the enthusiasm of stakeholders for participating in the project, as well as the stability of the project's operations. This study identifies core stakeholders in CWSM projects of colleges/universities. Then, a preliminary benefit allocation model is constructed through the Shapley value method, risks are identified, and a modified model is developed based on the COWA-gray fixed weight clustering method. Finally, a CWSM project launched by a Chinese university is studied to verify the applicability of the modified model.